Acute pancreatitis associated with intravenous administration of propofol: evaluation of causality in a systematic review of the literature. (6th November 2018) - Haffar, Samir; Kaur, Ravinder Jeet; Garg, Sushil Kumar; Hyder, Joseph A; Murad, M Hassan; Abu Dayyeh, Barham K; Bazerbachi, Fateh
Abstract: Acute pancreatitis (AP) associated with intravenous administration of propofol has been described with unknown causal relation. We therefore assessed this causality in a systematic review. Multiple databases were searched on 16 August 2017; studies were appraised and selected by two reviewers based on a priori criteria. Propofol causality was evaluated with the Naranjo scale and Badalov classification. We identified 18 studies from 11 countries with a total of 21 patients, and the majority had adequate methodological quality. The median age was 35 years (range, 4–77) and 10 (48%) were males. Overall, propofol was administrated in 8 patients as sedative along with induction/maintenance of anesthesia in 13 patients; median dose was 200 mg, with intermediate latency (1–30 days) in 14 (67%). Serum triglycerides were >1000 mg/dL in four patients. Severe AP was observed in four patients (19%). AP recurrence occurred in one out of two patients who underwent rechallenge. Mortality related to AP was 3/21(14%). Propofol was the probable cause of AP according to the Naranjo scale in 19 patients (89%). Propofol-induced AP has a probable causal relation and evidence supports Badalov class Ib. Hypertriglyceridemia is not the only mechanism by which propofol illicit AP. Propofol-induced AP was severe in 19% of patients with a mortality rate related to AP of 14%. Future research is needed to delineate whether this risk is higher if combined with other procedures that portend inherent risk of pancreatitis such as endoscopic retrograde cholangiopancreatography.